PROFILE OF SELECTED SENSORIMOTOR SKILLS IN ADOLESCENT POPULATION 6-18 YEARS (GYMNASIUM, 2017)
There is a number of studies dealing with the timing of the movement, focusing on the adult population and the population with cerebellar symptoms as a Parkinsson disease or essential tremor (Bareš, 2014, p.67). They try to explain the causes of slowness and their relationship with age or stage of a disease. Our study tries to determine the dynamics of the development of sensorimotor skills, which is responsible for the adolescent brain during ontogenesis and puberty. We are testing only boys from each age 6 to 18. Subjects perform a special test on a PC with a length of about 45 minutes to test their response and timing of movement. Every subject has to deal with a number of tests in which the individual tries to hit a moving target, which appear on the screen at 3 different angles (0°, 15° and 30°) and at different speeds (accelerating, decelerating, constant). This whole at unpredictable intervals by rotation for 45 minutes. Test data will be later evaluated by statistic methods. Predictive motor timing suggests that the cerebellum plays an essential role in integrating incoming visual information with the motor output in a timely manner.